2018
DOI: 10.3390/ijms19020337
|View full text |Cite
|
Sign up to set email alerts
|

An in Vitro Study on the Effect of Combined Treatment with Photodynamic and Chemical Therapies on Candida albicans

Abstract: Candida albicans is the most commonly encountered human fungal pathogen, and it is traditionally treated with antimicrobial chemical agents. The antimicrobial effect of these agents is largely weakened by drug resistance and biofilm-associated virulence. Enhancement of the antimicrobial activity of existing agents is needed for effective candidiasis treatment. Our aim was to develop a therapy that combined biofilm disruption with existing antimicrobial agents. Photodynamic therapy (PDT) utilizing curcumin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
5
22
0
2
Order By: Relevance
“…However, the antimicrobial PDT effect in adherent C. tropicalis was a lot weaker than in planktonic C. tropicalis . Consistent with our previous study on C. albicans [25], this result fulfills our prediction that it is more difficult to eradicate C. tropicalis when it is forming biofilms.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, the antimicrobial PDT effect in adherent C. tropicalis was a lot weaker than in planktonic C. tropicalis . Consistent with our previous study on C. albicans [25], this result fulfills our prediction that it is more difficult to eradicate C. tropicalis when it is forming biofilms.…”
Section: Resultssupporting
confidence: 93%
“…As an alternative treatment, PDT is an efficient antitumor therapy. However, for antimicrobial therapies, the effect of PDT is limited, as has been previously reported [25,43], and this is confirmed in this work. One major problem in antimicrobial PDT is the poor solubility and limited cell penetration of photosensitizers [44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An experimental study with 21 PLWHA showed that fluconazole did not prevent recurrence of oral candidiasis when they were reevaluated within 30 days, whereas in patients receiving PDT, there was no recurrence of the lesion during the same reevaluation period 14 . The combination of PDT and fluconazole was effective in reducing C. albicans colonies in in vitro 10,11 and in vivo 12,13 studies. In this study, participants 015 and 018, respectively, received PDT/nystatin and PDT/ fluconazole exhibited a reduction in oral candidiasis severity ratings when reassessed after 14 days.…”
Section: Discussionmentioning
confidence: 95%
“…This technique has shown to be promising in reducing C. albicans colonies in in vitro [9][10][11] and in vivo 12,13 assays. PDT was also effective in the treatment of oral candidiasis in PLWHA, without causing side effects, both isolated 14 and when associated with topical antifungals 15 .…”
Section: Introductionmentioning
confidence: 99%